Pengaruh Pengendalian Diri Terhadap Perilaku Merokok Siswa Sekolah Menengah Pertama - Eko Salim; Mic Finanto Ario Bangun (Jurnal Kajian Ilmiah, 2024)
Self-control plays a role in deactivating spontaneous responses and reactions through considerations so that upcoming events can be anticipated before a behavior is formed, then guiding oneself towards a positive direction. Smoking behavior in junior high school students can be influenced by self-control as an internal factor. Through a quantitative approach with correlational analysis and linear regression, the aim of this study is to identify the influence of self-control on smoking behavior among junior high school students. The sampling method uses a non-probability sampling technique with sample determination using purposive sampling technique, involving 116 male students as respondents. The self-control measurement tool uses the self-control scale and the smoking behavior variable is adapted. The research results show that there is a negative relationship between self-control and smoking behavior among students of State Junior High School X.